Role of Phytopharmacy as Hepatoprotector in Chronic Hepatitis - Budi Herlianto; Syifa Mustika; Supriono - -; Bogi Pratomo; Harijono Achmad (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2014)
Background: Hepatitis is one of the health problems in Indonesia that require special treatment, in line with the increase of morbidity and mortality rate of this disease. Complications of hepatitis include liver cirrhosis and hepatocellular carcinoma. Indonesia, as a tropical country, has many medicinal plants that act as hepatoprotector, a substance that can protect liver from toxic agent. Use of medicinal plants is still considered as controversial treatment because there is still lack of studies. Medicinal plants with mix composition of phytopharmacy, such as: Curcuma xanthorrhiza, Arcangelesia flava, Nigella sativa, and Kleinhovia hospita show potency as hepatoprotector. The objective of this study is to analyse the function of phytopharmacy as hepatoprotector in chronic hepatitis.Method: This study is a clinical trial performed in the Gastroenterology Department and Outpatient Clinic in Saiful Anwar Hospital in May-June 2013. Chronic hepatitis B or C patients who have received antiviral therapy with 3 fold increase of the threshold value of transaminase level, were included in this study. In this study, patients consumed phytopharmacy tablet 3 times per day. After 7 days of treatment, patients’ serum transaminase levels (ALT and AST) were re-assessed. Statistical analysis of before and after treatment data was performed using Wilcoxon test and the result was significant with p 0.05.Results: From 10 patients, the average age was 50.3 years old. Sixty percent (60%) of them were male, with 50% suffered from chronic hepatitis B and the other 50% suffered from chronic hepatitis C. From this study, decrement of alanine transaminase (ALT) and aspartate transaminase (AST) after seven days of treatment were 45.06%, with p = 0.007 and 48.63%, with p = 0.007, respectivelyConclusion: Phytopharmacy supplementation in chronic hepatitis can decrease serum transaminase, however further study is needed. Keywords: chronic hepatitis, phytopharmacy, ALT, AST, hepatoprotector